Solve for f 5(3f-2)+4f=23+3f

Math
5(3f-2)+4f=23+3f
Simplify 5(3f-2)+4f.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
5(3f)+5⋅-2+4f=23+3f
Multiply 3 by 5.
15f+5⋅-2+4f=23+3f
Multiply 5 by -2.
15f-10+4f=23+3f
15f-10+4f=23+3f
Add 15f and 4f.
19f-10=23+3f
19f-10=23+3f
Move all terms containing f to the left side of the equation.
Tap for more steps…
Subtract 3f from both sides of the equation.
19f-10-3f=23
Subtract 3f from 19f.
16f-10=23
16f-10=23
Move all terms not containing f to the right side of the equation.
Tap for more steps…
Add 10 to both sides of the equation.
16f=23+10
Add 23 and 10.
16f=33
16f=33
Divide each term by 16 and simplify.
Tap for more steps…
Divide each term in 16f=33 by 16.
16f16=3316
Cancel the common factor of 16.
Tap for more steps…
Cancel the common factor.
16f16=3316
Divide f by 1.
f=3316
f=3316
f=3316
The result can be shown in multiple forms.
Exact Form:
f=3316
Decimal Form:
f=2.0625
Mixed Number Form:
f=2116
Solve for f 5(3f-2)+4f=23+3f

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top